Analysis Market Orientation and Knowledge Management to Improve Innovation and Business Performance - Meylananda, Siti; Sarkum, Sumitro; Halim, Abd. (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
UMKM is a form of business that has an import rple in contributing income and helping to increase the regional economy. This study aims to explain the factors that influence innovation and business performance, namely customer orientation, competitor orientation, technology orientation, and knowledge management. In determining the sample of this study using using Non-Probability analysis method with saturation sampling technique, that the method of sampling by including all members as the research sample. So the respondents who have been determined are all members who have joined the Labuhanbatu UMKM House. As well as using the slovin formula with an error rate of 5%, so that the study sample amounted to 142 respondents. To analyze it using a path analysis tool assitessted by the SPSS and AMOS applications. The results of this study have seven influences were customer orrientation towards innovation and customer orrientation towards business performance. So it can be concluded that this study shows the role of strategic orientation which is required to increasingly innovate in improving business performance.